Spatiotemporal forest and land cover change in Türkiye: The role of economic factors in driving environmental transformations - Şen, Gökhan; Aktürk, Emre (Turkish Journal of Forestry, 2024)
Industrial advancements, urbanization, climate change, economic developments, and numerous other factors significantly influence land use preferences, subsequently causing changes in land cover. However, these changes are not homogeneus at the country scale. In this study, we aim to determine the total and provincial-based land cover changes in Türkiye between 2006 and 2018 and the impacts of macroeconomic variables on these changes. The land cover status for 2006 and 2018 and the changes occurring during this period were determined according to the Coordination of Information on the Environment (CORINE) system. For this purpose, five land cover classes were used. Correlation analysis was utilized to identify relationships between macroeconomic variables and cover changes and regression analysis was used to develop models aiming to predict future changes in land cover based on macroeconomic variables. Research findings indicate that 5.31% of forest areas, 2.9% of agricultural areas, and 7.19% of shrub and/or herbaceous vegetation associations have been converted to other uses. During this period, forest cover increased in 38 provinces in Türkiye, decreased in 41 provinces, and remained unchanged in two provinces. The province with the highest percentage increase in forest areas was Iğdır, at 19.98%, while the province with the most significant percentage decrease in forest areas was Ordu, at 0.62%. There was a statistically significant negative correlation between changes in forest areas and certain macroeconomic factors: gross domestic product (-0.310), number of automobiles (-0.308), number of motor vehicles (-0.326), and the number of buildings according to the building use permit (-0.287).
Keywords: 2. Zero hunger; 13. Climate action; 11. Sustainability; 15. Life on land